Contributions Of Locust Bean (Parkia Biglobosa, Jacque Benth) Seeds Production And Marketing To The Household Economy Of Kajola Local Govemment Area, Oyo State, Nigeria, (2005)
The study focused on the contributions of production and marketing of Locust bean (Parkia biylobosa, Jacque benth) seeds to the household economy in Kajola Local Government, area, Oyo state Nigeria, with a view to evaluating the percentage of population engaged in its production and marketing, and hence its contribution to rural employment and income generation as well as the proportion and frequency of consumption in local diets. Data were collected through the use of structured questionnaires. A total of 136 questionnaires were administered using stratified random sampling. The data generated were analyzed using descriptive statistics, cross tabulation and chi-square analyses. It was found out that about 47% of the respondents are involved in the commercial production of the species to supplement farm income. The product plays a crucial role in household food security in the study area as majority of the respondents (95.6%) consume it as part of their meals while 91.7% consume it at least once every other day. Although Chi-square test indicated that its contribution to household income is not significant(P> 0.523) its contribution to the household economy is very important as the fund comes handy during emergency cash needs and as an important supplement to farm income. Similarly Chi square test indicated that the quantity of iru consumed as a proportion of total quantity of household food intake is no significant (P>.0.063). However, chi-square value for preference for ‘Iru’ was significant (P> 0.001 indicating that majority of the respondents has preferential taste for iru against other condiments. It is recommended that research on silvicultural and conservation techniques be carried out on this species to ensure its sustained production